Clinical impact of MDR1-expression in testicular germ cell cancer - Schrader, A.J.; Seger, M.; Konrad, L.; Olbert, P.; Hegele, A.; Hofmann, R.; Heidenreich, A. (Experimental Oncology, 2007)
Aim: The multidrug resistance protein 1 (MDR1, P-gp, p-170) is a membrane glycoprotein that acts as an energy-dependent drug efflux pump. In various malignancies its expression is associated with resistance to diverse cytostatic drugs, and therefore predicts resistance to systemic treatment. The aim of this study was to investigate the prognostic value of MDR1 expression in primary tumor tissue to predict necrosis or viable cancer in residual tumor masses after systemic chemotherapy for advanced testicular germ cell cancer. Materials and Methods: Out of 77 patients, histopathological characteristics of primary testicular cancer specimens and retroperitoneal lymph node dissection (RPLND) samples following chemotherapy were available from 72 and all 77 patients, respectively. Moreover, MDR1 expression was determined by immunohistochemistry in 47 primary tumors and corresponding 73 RPLND sections. Results: After chemotherapy and subsequent RPLND, the examination of residual tumor masses revealed that mature teratoma and active viable tumor were predominantly found in patients with non-seminoma (NSGCT; p = 0.048), especially in those with containing mature teratoma (p = 0.001). Moreover, using univariate analysis the expression of MDR1 in the primary testicular tumor predicted viable tumor/teratoma residues in RPLND sections (p = 0.003). However, in multivariate analysis including the tumors’ histological subtype, MDR1 expression alone failed to reach statistical significance as an independent prognostic marker for residual vital tumor (p ≥ 0.16). Conclusions: With the limited number of patients given, the correlation between MDR1 expression in primary testis cancer and active residual retroperitoneal disease after chemotherapy failed to reach statistical significance as in independent marker. Therefore, up to now routine MDR1 staining of testicular germ cell cancer samples should not be performed in clinical practice. However, as there was a clear trend, a larger number of patients suffering from metastatic non-seminomas should be studied, as MDR1 expression might have significant prognostic value in this particular subgroup of patients.